Detection rate of colorectal cancer by routine colonoscopy is comparable in patients aged 45–49 and 50–54 years (Swiss Medical Weekly, 2024)
OBJECTIVES: Colorectal carcinoma remains one of the most common malignancies worldwide. Colonoscopy screening is most effective for early detection and tumour prevention and is currently recommended in Europe for adults aged over 50 years. However, given that an increasing proportion of patients are diagnosed before the age of 50, we set out to determine the detection rate of colorectal carcinoma in patients younger than 50 years and to determine the best threshold for starting colonoscopy screening.METHODS: Single-centre, retrospective cohort study of all colonoscopies performed, regardless of indication, in our department at a tertiary Swiss university hospital in patients aged ≥18 and